MECONIUM ILEUS AS INITIAL PRESENTATION OF CYSTIC FIBROSIS: A RETROSPECTIVE CASE SERIES FROM A MACEDONIAN PEDIATRIC CYSTIC FIBROSIS CENTER - Krsteska, Elena; Spirevska, Lidija; Andreevska Stepanovska, Andrijana; Anastasovska, Violeta; Jordanova, Olivera; Cvejoska Cholakovska, Valentina; Fushtikj Naceva, Stojka (University Ss. Cyril and Methodius in Skopje, 2025)
Introduction: Meconium ileus (MI) is often the earliest clinical sign of cystic fibrosis (CF), caused by intestinal obstruction due to thickened meconium from CFTR dysfunction. MI is commonly associated with severe CFTR mutations (classes I-III), which impair chloride and bicarbonate transport. Case report: We report a retrospective case series of six neonates with MI, diagnosed with CF at Pediatric CF Center at University Children’s Clinic, Skopje, over the last eight years. During this period, newborn bloodspot screening (NBS) program for CF was conducted, based on two sequential measurements of immunoreactive trypsinogen (IRT) and IRT-IRT protocol. All infants presented with early intestinal obstruction requiring surgical intervention, including enterotomy and ileostomy. Postoperative care included pancreatic enzyme therapy and nutritional support. CF diagnosis was confirmed via sweat chloride testing and genetic analysis, which showed a predominant presence of the F508del mutation in homozygous or compound heterozygous forms. Despite timely surgical intervention, three infants experienced severe complications and early mortality. It is noteworthy that one of these cases had false-negative NBS result, highlighting limitations of the IRT-IRT protocol in MI cases. The remaining patients showed varied recovery and nutritional outcomes. Conclusions: MI is a known cause of false-negative results in CF NBS, as IRT levels may be low in affected neonates. Therefore, any newborn presenting with MI should be presumed to have CF until proven otherwise. Confirmation requires sweat chloride testing and genetic analysis. These findings support the need for revised CF NBS protocols in all MI cases to ensure timely diagnosis and management.
Keywords: cystic fibrosis; immunoreactive trypsinogen; meconium ileus; newborn screening